2021
DOI: 10.3390/antiox10081188
|View full text |Cite
|
Sign up to set email alerts
|

Noise-Induced Cochlear Damage Involves PPAR Down-Regulation through the Interplay between Oxidative Stress and Inflammation

Abstract: The cross-talk between oxidative stress and inflammation seems to play a key role in noise-induced hearing loss. Several studies have addressed the role of PPAR receptors in mediating antioxidant and anti-inflammatory effects and, although its protective activity has been demonstrated in several tissues, less is known about how PPARs could be involved in cochlear dysfunction induced by noise exposure. In this study, we used an in vivo model of noise-induced hearing loss to investigate how oxidative stress and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…However, in most of the studies to date, the focus was on the protective effect of ALA rather than its rescue effect. Because oxidative damage is considered a cause of acute inner ear diseases such as ISSNHL and NIHL [ 29 , 32 ], studies in which antioxidants are used for hearing rescue are needed. Therefore, the present study was conducted, and results showed IT administration of ALA was safe and had a better hearing rescue effect with higher concentration of the drug in the cochlea com-pared with IP administration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, in most of the studies to date, the focus was on the protective effect of ALA rather than its rescue effect. Because oxidative damage is considered a cause of acute inner ear diseases such as ISSNHL and NIHL [ 29 , 32 ], studies in which antioxidants are used for hearing rescue are needed. Therefore, the present study was conducted, and results showed IT administration of ALA was safe and had a better hearing rescue effect with higher concentration of the drug in the cochlea com-pared with IP administration.…”
Section: Discussionmentioning
confidence: 99%
“…Various action mechanisms of the two drugs may explain the different expression levels of the inflammatory markers within the cochlea between the IT-ALA and IT-DEX groups. IL-1ß and NF-κB are inflammatory markers activated due to ROS stimulation induced by acoustic trauma [ 29 ]. In a previous study, a biphasic elevation of IL-1ß was reported after acute acoustic trauma: the first peak at 6 h and the second peak at 7 days after noise exposure [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When used with gentamicin in in vitro studies conducted by Sekulic-Jablanovic et al, pioglitazone demonstrated a protective cochlear effect against oxidative stress and prevented gentamicin toxicity [67,68]. As PPARs are involved in noise exposure cochlear damage [69], Paciello et al used pioglitazone in a biocompatible thermogel via transtympanic injection in rats with noise-induced hearing loss [70]. The authors documented a diminished ABR threshold shift and decreased hair cell loss in the middle-basal turn, but no considerable effect was noted in the apical cochlear turn.…”
Section: Pioglitazone (Antioxidant)mentioning
confidence: 99%